Aripiprazole for the treatment of irritability and aggression in children and adolescents affected by autism spectrum disorders. (2nd August 2016) - Rizzo, Renata; Pavone, Piero
ABSTRACT: Introduction : Aripiprazole is an atypical antipsychotic approved for the treatment of irritability and aggression in children and adolescents aged 6-17 years with autism spectrum disorder. Areas covered : This review will discuss the drug profile as well as available studies of aripiprazole in individuals with autism spectrum disorder as documented in prospective randomized controlled trials. Expert commentary : The heterogeneity of autism spectrum disorder has implications for assessing the effectiveness and safety of aripiprazole as it may not produce the same results in two individuals with the same diagnosis but different etiologies. Subgrouping of patients according to their overall presentation of symptoms may therefore be warranted. In addition, consideration should be given to the potential causes of irritability and aggression, such as coexisting medical conditions and environmental factors including inappropriate intervention of parents and teachers. In these cases, the identification of the underlying cause is important because the appropriate management.